You are on page 1of 7

MATHEMATICS IIB CIRCLE

1.

2 + 2 + 2 2 + 2 3 + (11) = 0

Find the equation of the circle passing through


points (3, 4), (3, 2), and (1, 4)

Sol: Let A (3, 4), B (3, 2), and C (1, 4)

+ + =

2.

Show that the points (1, 1), (-6, 0), (-2, 2) and (-2, 8) are concyclic.

Let the required eqn of the circle be


+ + + + =

Sol: Let A (1, 1), B (-6, 0), C (-2, 2) and D (-2, -8)

A (3, 4) lies on S=0,

Let the required eqn of the circle be

(3)2 + (4)2 + 2 3 + 2 4 + = 0

+ + + + =

9 + 16 + 6 + 8 + = 0

A (1, 1) lies on S=0,

+ + + = . ()

(1)2 + (1)2 + 2 1 + 2 1 + = 0

B (3, 2) lies on S=0,

1 + 1 + 2 + 2 + = 0

(3)2 + (2)2 + 2 3 + 2 2 + = 0

+ + + = . ()

9 + 4 + 6 + 4 + = 0

B (-6, 0) lies on S=0,

+ + + =

(6)2 + (0)2 + 2 6 + 2 0 + = 0

C (1, 4) lies on S=0,

36 + 0 12 + 0 + = 0

(1)2 + (4)2 + 2 1 + 2 4 + = 0

+ + + =

1 + 16 + 8 + 0 + = 0

C (-2, 2) lies on S=0,

+ + + = . . ()

(2)2 + (2)2 + 2 2 + 2 4 + = 0

Solving eqn (1) & (2)

4 + 4 4 + 4 + = 0

6 + 8 + + 25 = 0

+ + + = . . ()

6 + 4 + + 13 = 0

Solving eqn (1) & (2)

0 + 4 + 12 = 0 { 4}

2 + 2 + + 2 = 0

+ + = . ()

12 + 0 + + 36 = 0

Solving eqn (2) & (3)

14 + 2 34 = 0

6 + 4 + + 13 = 0

+ = . ()

2 + 8 + + 17 = 0

Solving eqn (2) & (3)

4 4 4 = 0 { 4}

12 + 0 + + 36 = 0

= . ()

4 + 4 + + 8 = 0

Solving eqn (4) &

8 4 + 28 = 0

(5)

{ 2}

{ 4}

+ = . ()

-1

-1

Solving eqn

(g, f)=

1+3 3+0
01

01

1 1

= (2, 3)

Sub g and f values in eqn (1)

(4 ) &

(5)

-17

-7

(g, f)=

7+17 34+49
72

72

10 15
5

= (2, 3)

6(2) + 8(3) + + 25 = 0

Sub g and f values in eqn (1)

12 24 + 25 + = 0 = 11

2(2) + 2(3) + + 2 = 0

, = 0

4 + 6 + 2 + = 0 = 12

MATHEMATICS IIB CIRCLE


, = 0

Solving eqn (2) & (3)

2 + 2 + 2 2 + 2 3 + (12) = 0

0 + 2 + + 1 = 0
8 + 10 + + 41 = 0

+ + + =
Since D (-2, -8) also lies on S=0

8 8 40 = 0

{ 8}

+ + = . ()

(2)2 + (8)2 + 4(2) + 6(8) 12


=4 + 64 8 48 12
= 68 68 = 0
.

3.

Solving eqn

(4) & (5)

-2

If (2, 0), (0, 1), (4, 5) and (0, c) are concyclic, and
then find the value of c.
103 320

Let the required eqn of the circle be

Sub g and f values in eqn (1)

+ + + + =

4(

(2)2 + (0)2 + 2 2 + 2 0 + = 0
4 + 0 + 4 + 0 + = 0

4+2

13
6

26
3

17

(g, f)=

A (2, 0) lies on S=0,

13

Sol: Let A (2, 0), B (0, 1), C (4, 5) and D (0, c)

4+2

)++4= 0

4=

2612

14
3

, = 0
2 + 2 + 2

+ + + = . ()
13

2 + 2

13

+2

17

17

14

+( )=0

6
14
3

=0

B (0, 1) lies on S=0,


(0)2 + (1)2 + 2 0 + 2 1 + = 0

Since D (0, c) also lies on S=0

0 + 1 + 0 + 2 + = 0

(0)2 + (c)2

+ + + =

17
3

13
3

14
3

(0)

17
3

=0

3c 2 17c + 14 = 0
C (4, 5) lies on S=0,
(4)2 + (5)2 + 2 4 + 2 5 + = 0
16 + 25 + 8 + 10 + = 0
+ + + = . . ()

3c 2 3c 14c + 14 = 0
3c[c 1] 14[c 1] = 0
1 3 14 = 0
1 = 0 3 14 = 0
= 1 =

Solving eqn (1) & (2)


4 + 0 + + 4 = 0
0 + 2 + + 1 = 0
4 2 + 3 = 0
+ = . ()

14
3

() +

14
3

=0

MATHEMATICS IIB CIRCLE


4.

Find the equation of the circle whose centre lies on


X-axis and passing through
(-2, 3), (4, 5)

5.

Find the equation of the circle passing through


points (4, 1), (6, 5)and whose centre lies on the
line + = .

Sol: Let A (-2, 3), B (4, 5)

Sol: Let A (4, 1), B (6, 5)

Let the required eqn of the circle be

Let the required eqn of the circle be

+ + + + =

+ + + + =

A (-2, 3) lies on S=0,

A (4, 1) lies on S=0,

(2)2 + (3)2 + 2 2 + 2 3 + = 0

(4)2 + (1)2 + 2 4 + 2 1 + = 0

4 + 9 4 + 6 + = 0

16 + 1 + 8 + 2 + = 0

+ + + = . ()

+ + + = . ()

B (4, 5) lies on S=0,

B (6, 5) lies on S=0,

(4)2 + (5)2 + 2 4 + 2 5 + = 0

(6)2 + (5)2 + 2 6 + 2 5 + = 0

16 + 25 + 8 + 10 + = 0

36 + 25 + 12 + 10 + = 0

+ + + =

+ + + =

Solving eqn 1 & 2

Solving eqn 1 & 2

4 + 6 + + 13 = 0

8 + 2 + + 17 = 0

8 + 10 + + 41 = 0

12 + 10 + + 61 = 0

12 4 28 = 0 { 4}

4 8 44 = 0 { 4}

+ + = . ()

+ + = . ()
, 4 + 3 24 = 0

(, )

4 + 3 24 = 0

. . , =

+ + = ()

= 0 (3)

Solving eqn 3 & 4

3 + 0 + 7 = 0

11

3 = 7

24

(g, f)=

Sub g and f values in eqn (1)


3

+ 13 + = 0 =

2839
3

67

7
3

15
5

20
5

8(3) + 2(4) + + 17 = 0
24 8 + 17 + = 0 = 15

67

+2 0 +( )=0

( + ) =

38

, = 0
2 + 2 + 2

(1)

4( ) + 6(0) + + 13 = 0
28

38

= (3, 4)

4833 4424

, = 0
2 + 2 + 2 3 + 2 4 + (15) = 0
+ + = .

MATHEMATICS IIB CIRCLE


7.
Show that the circles + + =
, + + + = touch each other.
Find the point of contact and eqn of tangent at
point of contact.

6.

Sol: eqn s of the given circles


x2

+ y2

Show that the circles


+ = , + + +
+ = touch each other. Find the point of

contact and eqn of tangent at point of contact.


Sol: eqn s of the given circles
S x 2 + y 2 4x 6y 12 = 0 . . (1)

6x 2y + 1 = 0 . . (1)

S x 2 + y 2 + 6x + 18y + 26 = 0 . . (2)

S x 2 + y 2 + 2x 8y + 13 = 0 . . (2)
, : C1 3, 1 ,

, : C1 2, 3 ,

=
+

=
1 =

32

+ 12

2 =

12

42

1=

1 = 22 + 32 + 12 = 4 + 9 + 12 = 5

=3

2 = 32 + 92 26 = 9 + 81 26 = 64 = 8

13 = 17 13 = 4 = 2

(2 1 )2 + (2 1 )2

1 2 =
=

32

1 3

+ 41

1 2 =
=

1 2 Internally in the
ratio 1 : 2 = 3: 2 = :

2 + 1 2 +1

3+6 12+2

x2

3+2

(5)2 + (12)2 = 25 + 144 = 169=13

.
1 2 Internally in the
ratio 1 : 2 = 5: 8 = :

3+2

P=

2 + 1 2 +1

5 3 +8(2) 5 9 +8(3)
5+8

5+8

3 14
5

y2

6x 2y + 1 = 0

y2

+ 2x 8y + 13 = 0

+ 93

3 1 +2(3) 3 4 +2(1)

= 0
x2

1 2 = 1 + 2

3 2

1 2 = 1 + 2

P=

(2 1 )2 + (2 1 )2

(4)2 + (3)2 = 25 =5

C2 3, 9

C2 1, 4

-8x+6y -12=0 { 2}
4 3 + 6 = 0.

15+16 45+24
13

1
13

21
13

= 0

x 2 + y 2 4x 6y 12 = 0
x 2 + y 2 + 6x + 18y + 26 = 0
-10x-246y -38=0 { 2}
5 + 12 + 19 = 0.

MATHEMATICS IIB CIRCLE


8.

Find the transverse common tangents of the circles

4 18 = 3 + 3

+ + = , + +
+ = .

3 + 4 21 = 0.

Sol: eqn s of the given circles

3 + 4 21 = 0 1 = 0.

S x 2 + y 2 4x 10y + 28 = 0 . . (1)

9.

x2

y2

Find the direct common tangents of the circles


+ + = , +
+ + = .

+ 4x 6y + 4 = 0 . . (2)

, : C1 2, 5 ,

C2 2, 3

Sol: eqn s of the given circles

S x 2 + y 2 + 22x 4y 100 = 0 . . (1)

1 = 22 + 52 28 = 4 + 25 28 = 1

S x 2 + y 2 22x + 4y + 100 = 0 . . (2)

, : C1 11, 2 , C2 11, 2

2 = 22 + 32 4 = 4 + 9 4 = 9 = 3

2 2

+ 35

= 225 = 15

= 25 = 5

. .
1 2
Internally in the ratio 1 : 2 = 1: 3 = :
2 + 1 2 +1

2+6 3+15

112 + 42 100 = 121 + 4 100

2 =

1 2 > 1 + 2

P=

112 + 22 + 100 = 121 + 4 + 100

1 =

(4)2 + (2)2 = 16 + 4 = 20

4 18
4

(2 1 )2 + (2 1 )2

1 2 =
=

1 2 +3(2) 1 3 +3(5)
1+3

(2 1 )2 + (2 1 )2

1 2 =

1+3

11 + 11

(22)2 + (4)2 = 484 + 16 = 500

= (1, )

1 2 > 1 + 2

. .
9

Eqn of tangent is 1 = ( 1 ) (1, )


2

= 1

2 9
2

1 +1 +

2 1
4 2 +4

=1

And

1
0
9
2

44 8
2

31

31

= (22, 4)

2 1 = 2
=

1 1=0
=

3
4

1 +1 +
2 + 2

11 1 2 22 4
( )2 +(1)2

3 11 1(11) 3 2 1(2)

22 4 = 0 (1)
=

S.O.B.S

3 = 4 =

+ 4 = 22 + 4 = 22

=1

42 + 1 4 = 42 + 4

33+11 62

(2 1)2 = 42 + 4

Eqn of tangent is 1 = ( 1 ) (22, 4)

2 + 2

2 (2)2(5)2 +9

2 + 1 2 +1

P=

1 1 = 1

(2 )2 +(2)2

1 2
Internally in the ratio 1 : 2 = 15: 3 = 3: 1:

= 1

2 2 2 + 9 = 0 (1)
=

+ 2 2

11 2
2 +1

=5

=5
S.O.B.S

(11 + 2)2 = 25(2 + 1)


1212 + 4 + 44 = 252 + 25

MATHEMATICS IIB CIRCLE


962 + 44 21 = 0

11. If , are the angles of inclination of tangents


through a point p to the circle x2+y2=r2, then find
locus of p when cot + =k.

962 + 72 28 21 = 0
24 4 + 3 7(4 + 3) = 0
24 7 4 + 3 = 0
24 7 = 0 4 + 3 = 0
7

24

, =

3
4


+4 =

7
24

22 24 + 96 = 7 156

7 24 250 = 0.
And
+4 =

3
4

22 4 + 16 = 3 + 66

3 + 24 50 = 0.

Sol: given equation of the circle x2+y2=r2.


(1)
: Let P(x1, y1) be the any point on the locus
Equation of tangent through p with slope m is
Y= 1 + 2
This passes through P(x1, y1)
1 =1 1 + 2
1 -1 = 1 + 2
S.O.B
(1 1 )2 = ( 1 + 2 )2
1 2 + 2 1 2 21 1 = 2 (1 + 2 )
1 2 + 2 1 2 21 1 = 2 + 2 2 )
2 1 2 2 21 1 + 1 2 2 = 0
Where m1, m2 be the slopes of the tangents
which make angles 1 , 2
m1=tan1 , m2=tan2
Given cot1 + cot 2 =k.

3 + 24 50 = 0 7 24 250 = 0.

1 2
1
1

1 2

2 1

1 2

1 + 2 = 1 2

10. Find the equation of the circles which touch


2x-3y+1=0 at (1, 1) and having radius .
Sol: given two circles touch the line
2 3 + 1 = 0 (1)
(1, 1)
= 13
The centres
1 , 2
1 1 , 1 = (1, 1)
2

3
3

Slope of (1) = - ( ) =
Slope of line 1 2 =
3

= =
=

3
13

2
13

The centres 1 , 2
= 1 , = 1
= 1 13

2
13

, 1 13

3
13

= {1(2), 1 3}
= (1-2, 1+3) and (1+2, 1-3)
= (-1, 4) and (3, -2)
Eqn of the circle with 1 1, 4
= 13
2

( + 1)2 +( 4)2 = 13
x 2 + y 2 + 2x 8y + 4 = 0
Eqn of the circle with 2 3, 2
= 13
( 3)2 + ( + 2)2 = 13
x 2 + y 2 6x + 4y = 0.

2 1 1
1 2 2

1 2 2

1 2 2
(1 2 2 )

21 1 =
The equation of locus of P(x1, y1) is
2 = ( 2 2 )

12. Show that the poles of tangents to the circle


x2+y2=r2 w.r.to the circle (x + a) 2+y2=2a2 lie on
y2+4ax=0.
Sol: Let P(x1, y1) be the pole of tangents of the
circle x2+y2=r2 w. r. to the circle S(x + a)
2+y2=2a2
x 2+y2 +2ax-a2=0
Now the polar of p w.r.t to S=0 is S1=0
xx1+yy1+a(x+x1) - a2=0
x(x1+a) +yy1+ (ax1- a2) =0.. (1)
1 + + = 0,
= 1 + , = 1 , = 1 a2
+ + = 0
2 + 2 = 2 2 = 2 ( 2 + 2 )
(1 2 )2 = 2 {(1 + )2 + 1 2 }
2
{ 1 2 = 2 {(1 + )2 + 1 2 }
1 2 + (1 + )2 (1 )2 = 0 1 2 +
41 = 0
the equation of locus of P(x1, y1) is y2+4ax=0

MATHEMATICS IIB CIRCLE


13. If the chord of contact of a point P with respect to

the circle x2+y2=a2 cut the circle at A and B such


that AOB =900 then show that P lies on the circle
x2+y2=2a2.
Sol: Given circle x2+y2=a2... (1)
Let p(x1, y1) be a point and let the chord of
contact of it cut the circle in A and B such that
AOB=900. The equation of the chord of contact
of p(x1, y1) with respect to (1) sis xx1+yy1a2=0.. (2)
The equation to the pair of lines OA and OB is
given by x2+y2-a2

1 + 1 2
2

=0

Or 2 x 2 + y 2 1 + 1 2 = 0
2 2 1 2 21 1 + 2 2 1 2 = 0
(3)
Since AOB=900, we have the coefficient of
2 3 + 2 3 = 0
2 1 2 + 2 1 2 = 0
1 2 + 1 2 = 22
Hence the point p(x1, y1) lies on the circle
x2+y2=2a2.

14. Prove that the combined equation of the pair of


tangents drawn from an external point p ( , )
to the circle S=0 is = .
Sol: given that p (x1 , y1 ) is an external point on
S=0 let AB be the chord of contact of P to the
circle S=0 and its equation is 1 = 0
Let Q (x2 , y2 ) be any point on the locus
i.e. , be a point on the pair of tangents
the ratio that the line AB divides PQ can be
determined in 2ways :
(1) PB:QB is equal to 11 : 22 .(1)
(2) The line
1 =
0
11

Points p (x1 , y1 ), Q (x2 , y2 ) in the ratio-

12

(2)
From (1), (2) we get

11
22

11

11
22

11
12

S.O.B

12 2

11 22 = 12 2
Hence the equation of the locus of
Q (x2 , y2 ) is S1 2 = SS11 .
{ (x2 , y2 ) replaced by (x, y)}